An Algebraic Method on the Eigenvalues and Stability of Delayed Reaction-Diffusion Systems - Jian Ma; Baodong Zheng (Discrete Dynamics in Nature and Society)
The eigenvalues and stability of the delayed reaction-diffusion systems are considered using the algebraic methods. Firstly, new algebraic criteria to determine the pure imaginary eigenvalues are derived by applying the matrix pencil and the linear operator methods. Secondly, a practical checkable criteria for the asymptotic stability are introduced.